Multilingualism and mismatching: Spanish language usage in college admissions essays - Alvero, AJ; Pattichis, Rebecca (Poetics (Amsterdam), 2024)
In US K-12 education, the Spanish language is subject to practices and policies that limit its expression, especially among racialized Latinx students. However, higher education claims to view Spanish as a positive form of diversity. We therefore examine college admissions essays to analyze how students strategically deploy Spanish in light of these contradictions. We use two years of undergraduate application essays (n = 276,768) and metadata submitted to the University of California by every self-identified Latinx applicant and a racially representative random sample of non-Latinx applicants. To identify Spanish language usage in the text, we develop a computational mixed methods approach by combining machine translation and human reading. Spanish was used by 33% of Latinx and 15% of non-Latinx students with stylistic variation by class and ethnicity. We also find that lower income Mexican and Central American applicants were the most likely to use substantive forms of Spanish in their admissions essays as well as provide translations into English. We posit that this self-translation is an example of students identifying cultural mismatch between themselves and university admissions offices. This linguistic strategy, which we call strategic Spanish, sheds light on how language, culture, and ethnicity intersect in high-stakes evaluation and also helps surface the potential for machine translation as a method for social scientific inquiry.